Changes in levels of urokinase receptor and other components of fibrinolytic system in brain tissues in urokinase gene-knockout mice with B16/F10 melanoma growing together with chronic neurogenic pain - E. M. Frantsiyants; V. A. Bandovkina; I. V. Kaplieva; N. D. Cheryarina; E. I. Surikova; I. V. Neskubina; Yu. A. Pogorelova; L. A. Nemashkalova (Исследования и практика в медицине, 2022)
Purpose of the study. An analysis of the changes in components of the urokinase system in the brain of urokinase gene-knockout mice (uPA-/-) with B16/F10 melanoma growing alone and together with chronic neurogenic pain (CNP).Materials and methods. The study included male and female C57BL/6-PlautmI.IBug-ThisPlau6FDhu/GFDhu mice (uPA-/-) (n = 48) and C57BL/6 mice (uPA+/+) (n = 80) with transplanted B16/F10 melanoma growing solitarily and together with CNP. Levels of the urokinase receptor (uPAR) and plasmin (PAP) and activity and levels of the PAI-I inhibitor were measured in the brain of animals by ELISA.Results. Levels of uPAR, PAI-I and PAP in the brain differed only in intact uPA-/- males, being on average 1.6 times higher (p < 0.05) than in uPA+/+ mice. Among animals with CNP, uPA-/- males showed increased PAI-I by 1.3 times (p < 0.05) and decreased PAP by 2.6 times (p < 0.05), while in uPA+/+ males, changes in PAI-I and PAP were opposite; in uPA-/- females, levels of all indicators increased by 1.6–2.1 times (p < 0.05), unlike uPA+/+ females. Among animals with melanoma only, changes in the levels of uPAR, PAI-I and PAP in the brain tissues in uPA-/- males differed from the group with CNP and from uPA+/+ males; in uPA+/+ females, levels of uPAR and PAP increased by 1.7 and 3.0 times (p < 0.05), and only PAP increased in uPA-/- females by 3.2 times (p < 0.05). Combination of CNP with melanoma in uPA-/- mice, regardless of their gender, down-regulated levels of uPAR and PAI-I on the average by 1.5 and 2.0 times, respectively (p < 0.05), and up-regulated PAP on the average by 2.2 times (p < 0.05) compared to the levels in animals with CNP; in uPA+/+ animals, similar decline of uPAR by 3.7 times (p < 0.05) was registered only in males, and an increase of PAI-I by 2.0 times (p < 0.05) was noted in all mice.Conclusion. Changes in the studied parameters in the brain tissue of urokinase gene-knockout animals in response to stress factors indicate the role of the brain urokinase system in the response to both CNP and melanoma growth, and the gender specificity of these changes may be another factor that conditions gender differences in the risk of occurrence and course of cutaneous melanoma.